Analisis Strategi Pembelajaran untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran IPS di Sekolah Dasar - Rama Alfigo; Adrias Adrias; Salmaini Safitri Syam (Pusat Riset dan Inovasi Nasional, 2025)
The teaching of Social Studies in elementary schools still faces challenges in improving students' understanding, primarily due to the dominance of expository methods that lack variety. This study aims to analyze various innovative learning strategies that can enhance students' comprehension in Social Studies education. The research employs a library research method with a qualitative approach, drawing on various references and previous research findings.The results indicate that contextual learning strategies, project-based learning (PjBL), technology integration, cooperative learning, and multi-representation learning are effective in improving students' understanding. Contextual learning enhances students' comprehension by up to 32%, while PjBL improves critical thinking and problem-solving skills. Technology integration, such as augmented reality and interactive digital media, has been shown to increase learning motivation by up to 43%. Cooperative learning and multi-representation strategies also positively impact social skills and conceptual understanding.The novelty of this study lies in its comprehensive mapping of innovative, evidence-based learning strategies applicable to Social Studies education in elementary schools. The implications of this research highlight the importance of innovation in teaching strategies to ensure that students do not merely receive information passively but can actively apply their knowledge in real-life situations. Additionally, the study underscores the need for teachers to enhance their competencies in implementing more interactive and student-centered teaching methods.